UMA SEQUÊNCIA DIDÁTICA PARA O ESTUDO DE TRANSFORMAÇÕES GEOMÉTRICAS - Refatti, Liliane Rose (2012)
In the present work was to investigate the contributions of Didactic engineering methodology along with the software GeoGebra and Cabri 3D in the understanding of the concept of geometrical transformation, in a class of graduate course in mathematics. Wondered if the Dynamic Geometry environments promote the development of geometric skills of students; if the interaction provided by software, helped in the process of knowledge construction concerning geometric transformations; and the way the students if appropriate tools and/or features of GeoGebra and Cabri 3D content in the learning of geometrical transformations. The methodology of the study relied on assumptions of Engineering Didactics to Artigue (1996). The subject search participants were students who attended the discipline of Geometry I, of course of degree in Mathematics. By analyzing the data obtained from observation of the teacher and of the buildings produced by students, as well as the questionnaire applied at the end of the survey, it was possible to verify that the interaction of students with the software when working with the sequence of elaborate activities facilitated the visualization and mental assimilation of concepts worked.